Empowering Women and Enhancing Climate Resilience Through Socio-Technical Innovation Bundles - CGIAR Initiative on Gender Equality (CGIAR, 2024)
The "EMPOWER" work package of the CGIAR Gender Equality Initiative is implementing socio-technical innovation bundles (STIBs) to tackle the challenges of climate change and food and nutrition insecurity for marginalized women farmers in different parts of India, Kenya, and Ethiopia. STIBs are systematically bundled and implemented social, technical and technological innovations to enhance climate resilience and promote gender equity in the agrifood systems. Described in English and Bengali, the videos illustrate how the STIBs can be tailored to the local contexts and can contribute to women's economic empowerment and build resilience to climate change. ENG - https://www.youtube.com/watch?v=CmVkSJBHQUs BEN- https://www.youtube.com/watch?v=CmVkSJBHQUs